ADVANCING PROTECTION AND INDEMNITY INSURANCE (P&I CLUBS): STRENGTHENING LEGAL PROTECTION FOR INDONESIAN CARRIERS - Abdullah, Mohd. Kamarulnizam; Rachmawati, Irma (Faculty of Law, Universitas Pasundan, 2023)
Sea transportation is inherently exposed to various risks, including vessel damage and marine pollution caused by collisions and accidents. These risks pose significant challenges to carriers, particularly when they fall outside the scope of traditional insurance coverage. To address such gaps, shipowners have established Protection and Indemnity (P&I) Clubs, mutual associations that provide comprehensive coverage for liabilities not covered by conventional underwriters. This study explores the critical role of P&I Clubs in protecting Indonesian carriers, focusing on their rules and operational impact. It also examines the distinctions between P&I Clubs and traditional marine insurance, highlighting their complementary roles. Employing a library research method with a dogmatic legal approach, the study utilizes diverse sources, including international conventions, domestic legislation, case law, legal literature, P&I Club rules, and reputable online resources. The findings reveal that P&I Clubs offer broader and more specialized coverage than standard marine insurance, particularly in addressing pollution-related accidents. For example, P&I Clubs cover the full scope of pollution impacts, providing a level of protection unavailable through other means. The novelty of this research lies in its focused analysis of P&I Club practices in the Indonesian context, offering insights into their unique contributions to maritime risk management. By bridging the gap between legal theory and practical application, this study underscores the urgency of integrating P&I Club mechanisms into Indonesia's maritime industry, contributing to enhanced carrier protection and risk mitigation strategies.